1975
DOI: 10.1104/pp.56.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Secretion of Maize Root Cap Slime

Abstract: The distribution of fucose-containing polysaccharides in apical 1-cm sections of corn (Zea mays cv. (3) showed that when the distribution of label appearing in fucose was expressed as a ratio of label in xylose, the ratio was higher in the apical 0.5-mm section of the root. An autoradiographic study by Kirby and Roberts (7) Figure 1. Twentyfive root tips and 1 ml of medium were removed from the incubation flask and washed four times with 1 ml of chilled distilled H20. The medium and washings were combined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Cytochrome oxidase was determined by adding an appropriate aliquot (10-50 ,lI) of particle suspension or gradient fraction to 0.5 ml of 20 ,uM reduced Cyt c in 50 mm tris buffer (pH 7.5), and following optical density at 550 nm with a recording spectrophotometer. NADH:-and NADPH:Cyt c reductases were assayed similarly but the medium contained 20 ,lM oxidized Cyt c, 80 ,mM NADH or NADPH, and 1 mm KCN.…”
Section: Methodsmentioning
confidence: 99%
“…Cytochrome oxidase was determined by adding an appropriate aliquot (10-50 ,lI) of particle suspension or gradient fraction to 0.5 ml of 20 ,uM reduced Cyt c in 50 mm tris buffer (pH 7.5), and following optical density at 550 nm with a recording spectrophotometer. NADH:-and NADPH:Cyt c reductases were assayed similarly but the medium contained 20 ,lM oxidized Cyt c, 80 ,mM NADH or NADPH, and 1 mm KCN.…”
Section: Methodsmentioning
confidence: 99%
“…Because the root-tip region is the site of the most intense mucilage production (Paul1 and Jones, 1975), immobilization of A1 in this layer could constitute an important mechanism that protects the meristem from A1 injury (Horst et al, 1982) through exclusion of A1 from the cell symplasm (Taylor, 1988(Taylor, , 1991. Chelate ligands present in the mucilage may bind A1 and thereby present a physical or chemical barrier to the inward movement of A1 (Henderson and Ownby, 1991).…”
mentioning
confidence: 99%
“…Chelate ligands present in the mucilage may bind A1 and thereby present a physical or chemical barrier to the inward movement of A1 (Henderson and Ownby, 1991). Enhanced exudation of malate (Delhaize et al, 199313;Basu et al, 1994b;Ryan et al, 1995a, 199513) and citric acid (Miyasaka et al, 1991;Pellet et al, 1995) have been reported in Al-resistant cultivars of T. aestivum, Phaseolus vulgaris, and Z. mays. Furthermore, Horst et al (1982) showed that 50% of total A1 in 5-mm root tips of V. unguiculata was bound to mucilage.…”
mentioning
confidence: 99%
“…Plant roots grown under Al stress secrete organic acids and moderate the toxicity of Al ions by chelation [24]. A viscous mucilage, consisting mainly of polysaccharides, is secreted from roots and may act as a barrier to Al toxicity [25,26]. Moderation by organic acids, proteins, and other ligands, accumulation of Al in vacuoles, and activation of Al-tolerant enzymes have been suggested as symplasmic tolerance mechanisms [27].…”
Section: Introductionmentioning
confidence: 99%